2007
DOI: 10.1111/j.1439-0310.2007.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg Colour Covaries with Female Expression of a Male Ornament in the Spotless Starling (Sturnus unicolor)

Abstract: The sexually selected egg colour hypothesis (SSECH) proposes that egg colouration is as a post‐mating sexually selected signal of female phenotypic quality, maintained by a higher allocation of paternal care. Similarly, some female traits can reflect genetic quality or condition and males could use this information in mate choice or in modulating parental investment. In our study, we examined the correlation of individual variation in egg colouration with female expression of a male ornament and how male feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
(81 reference statements)
1
25
0
1
Order By: Relevance
“…For example, males may attend to UV-reflectance of eggs as a predictor of female quality, as has been suggested in spotless starlings and garnering moderate, if correlative, empirical support (López-Rull et al 2007). Eggshells of extinct moa species are often found in caves, suggesting that UV egg reflectance may have facilitated egg location and recognition in these species.…”
Section: Functional Relevance Of Uv-sensitivity Among Paleognathsmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, males may attend to UV-reflectance of eggs as a predictor of female quality, as has been suggested in spotless starlings and garnering moderate, if correlative, empirical support (López-Rull et al 2007). Eggshells of extinct moa species are often found in caves, suggesting that UV egg reflectance may have facilitated egg location and recognition in these species.…”
Section: Functional Relevance Of Uv-sensitivity Among Paleognathsmentioning
confidence: 88%
“…Eggshells of extinct moa species are often found in caves, suggesting that UV egg reflectance may have facilitated egg location and recognition in these species. Ostrich, emu, and extinct stout-legged moa eggshells are known to reflect UV light (Igic et al 2010a) which may play a functional role in signaling quality of both mother and chicks in other species (Moreno et al 2005;López-Rull et al 2007. Fadzly et al (2009) has examined the spectral reflectance curves of lancewood tree (Pseudopanax crassifolius) leaves once exploited by moa species as a food source.…”
Section: Functional Relevance Of Uv-sensitivity Among Paleognathsmentioning
confidence: 99%
“…Similarly, Moreno et al (2008) found that nestling Pied Flycatchers from nests that received a single experimentally darker blue egg weighed more and were in better condition than those in control nests, suggesting that they received better parental care. In contrast, Krist and Grim (2007) found no relationship between blue egg color and parental investment by male Collared Flycatchers, and Lopez‐Rull et al (2007) found no relationship between egg brightness and the provisioning rates of male Spotless Starlings.…”
mentioning
confidence: 80%
“…) and to reproductive success in females (López‐Rull et al . ). In total, we were able to catch 197 adults (2005, 62 females and 49 males; 2006, 45 females and 41 males).…”
Section: Methodsmentioning
confidence: 97%